Some New Components of the Moduli Scheme MP3(2; -1; 2; 0) of Stable Coherent Torsion Free Sheaves of Rank 2 on P3 - M. A. Zavodchikov (Моделирование и анализ информационных систем)
In this paper we consider Giseker-Maruyama moduli scheme M := MP3(2;¡1; 2; 0) of stable coherent torsion free sheaves of rank 2 with Chern classes c1 = -1, c2 = 2, c3 = 0 on 3-dimensional projective space P3. We will de¯ne two sets of sheaves M1 and M2 in M and we will prove that closures of M1 and M2 in M are irreducible components of dimensions 15 and 19, accordingly.